Kinetic Study of Anodic Corrosion of Copper in Phosphoric Acid and Effects of Some Phenols Derivatives - Abdel-Haleem, S.M.; Ahmed, A.M.; Shadad, M.I. (Asian Journal of Chemistry, 2013)
Electropolishing of copper in phosphoric acid is considered as corrosion rate of copper and due to the economic importance of copper there are several researches deals with acceleration and inhibition of this process. From the previous studies, this process may be controlled by the presence of some materials which may cause acceleration or inhibition of this process. In this paper the electropolishing process inhibited with different ratio by addition of some organic phenols derivatives by addition with concentration (10-5-10-2 mol L-1). The results reveal that organic phenols have strongest inhibitive effect ranging from 4.92 to 40.98 % and the thermodynamic parameters and as well as adsorption isotherm were given.